Pengembangan Video Pembelajaran Berbasis Kearifan Lokal dalam Dimensi Mandiri Profil Pelajar Pancasila pada Anak Usia Dini di TKIT Mutiara Hati Kota Jambi - Annisaa Auliya Maghribi; Hendra Sofyan; Nyimas Muazzomi (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This development research aims to develop a learning video product based on local wisdom in the independent dimension of the Pancasila Student Profile. The research respondents were material and media experts as validators, seven Mutiara Hati Kindergarten Teachers, and six children in group B2. The research method used is the research and development method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Based on the results of the validity test from the material experts, the learning video reached a percentage of 89.6% with very good criteria. The validity test from the media experts showed that the learning video reached a percentage of 98.5% with very good criteria, while the feasibility test by seven Mutiara Hati Kindergarten Teachers obtained a percentage of 91.7% with very good criteria. The children's response in group B2 showed a percentage of 74.1% with good criteria. Thus, based on the results of the assessment, it can be concluded that the learning video product is appropriate and feasible to introduce local wisdom of the Jambi region and develop the independent dimension of the Pancasila Student Profile in children.